GAMBARAN TINGKAT PENGETAHUAN KELUARGA TENTANG PENYAKIT TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS SUKAMERINDU KOTA BENGKULU - Anggraini Anni (Jurnal Vokasi Keperawatan (JVK), 2022)
The increasing number of pulmonary tuberculosis patients in Indonesia is caused by a lack of public knowledge about pulmonary tuberculosis so that there are still many people who behave unhealthy. In addition, the level of family knowledge has a major influence on the health status of the family and the tuberculosis patient itself and plays an important role in the success of the prevention and prevention program for pulmonary tuberculosis. In 2021 cases of pulmonary tuberculosis patients at the Bengkulu City health office were reported to be 352 in adult patients and 33 in pediatric patients. The low success rate of pulmonary tuberculosis treatment in the city of Bengkulu is the low level of knowledge of families and tuberculosis sufferers in carrying out independent health care on a regular basis. This type of research uses a quantitative descriptive method. The purpose of this study was to describe the level of family knowledge about pulmonary tuberculosis in the Sukamerindu Public Health Center, Bengkulu City. This type of research uses a quantitative descriptive method. The research population was 37 respondents. The sampling technique used was total sampling. The research instrument used a questionnaire. The results showed that the level of family knowledge about pulmonary tuberculosis was in the good category 5%, in the sufficient category 57% and 38% in the less category. To increase public knowledge, it is necessary to provide health education and counseling about pulmonary TB.